Evaluasi Praktik Soal TOEFL Reading: Tips Efektif dan Contoh-Contoh Soal - Nurmala Septi; Ahmad Hafız Nawwali; M. Dzaky Faruq; M. Fakhruzzaini; Dea Putri Ananda; Chairun Najwa; Nazimah (Indo Publishing, 2025)
This research or article aims to provide a systematic guide for English language learners to evaluate and enhance their performance on the TOEFL Reading Section independently. While fundamental language proficiency serves as the foundation, the ability to self-correct and effectively apply test-taking strategies is the determining factor in achieving high scores. The material is focused on two key, integrated aspects: (1) Effective Test-Taking Tips and (2) Practice and Analysis of Sample Questions. The first section reviews various essential techniques, such as skimming for main ideas, scanning for specific details, and strategies for tackling questions involving implied meanings and vocabulary in context. The second section provides a simulation and in-depth analysis of different types of TOEFL Reading sample questions, allowing readers to practice, evaluate their results, and identify common error patterns. Through this structured self-evaluation approach, it is expected that readers will not only understand the question format but also be able to critically adopt the test-taking tips, leading to a significant improvement in their performance on the TOEFL Reading Section.